RANCANG BANGUN MODEL SISTEM PENGELOLAAN DOKUMEN DALAM PENINGKATAN PELAYANAN ADMINISTRASI PADA SUBBAGIAN TATA USAHA PIMPINAN DI BAGIAN PROTOKOL KABUPATEN LAMPUNG TIMUR - Elip Heldan; Eva Natalia Tamba (Universitas Bandar Lampung (UBL), 2019)
Documents are one of the important factors in measuring the level of achievement of organized activities in government. The development of science and technology currently causes changes in all aspects of life, as well as in administrative activities. At present many parties are utilizing electronic media in document management. Using electronic media in document management will facilitate data management.This research is an exploratory research with a system approach in the form of Soft System Methodology (SSM) which is an approach to solve complex unstructured problem situations. The analysis used is to use 7 (seven) stages in Soft System Methodology (SSM).From the results of the study it can be concluded that the management of documents to improve administrative services leadership can be done through the use of an input system for documents or letters electronically so as to streamline time, Lack of understanding of JFU in existing technology so that it is a bit difficult to implement the existing system, Lack of understanding of the manuscript service so that there is often a lack of understanding of correspondence. Requirement of protocol training for all protocols so that they can understand their respective duties and functions and Standard Operating Procedures that have not been optimal for managing incoming and outgoing letters and the absence of Standard Operating Procedures for the Secretary of the Regent.